(untitled) (Aporte Santiaguino, 2019)
The main objectives were: to program a software to calculate the costs of seasonal crop production per hectare; to create a database of inputs, written and verbal agriculture technical information for the central coastal areas, and to validate the software surveyed in a user satisfaction tested to students and academic staff involved into agriculture. It allow users to determine the sowing rate per hectare, number of fertilizer bags according to NPK formulas, the current input costs, investment costs and profitability in one cropping hectare. The software considered the income, user password, initial presentation, general information to register a crop, record of specific data defined by agriculture tasks, review, correction or adding data from direct and indirect costs, economic analysis, rate of return, final report in local currency (soles) or dollars, and printing the sheet production costs per hectare. It was concluded that 98 % of respondents said that the software was friendly and 84 %, it was a successful program to fill the needs of users engaged in agriculture. The software is friendly, easy to use and provides adequate support to users